IMPROVING BUSINESS STRATEGY FOR COMPOSTER BIN SALES: CASE STUDY OF PASMA - Dian Anggraini, Ranti
It is very concerning to see the growing waste in Indonesia every year. In 2020, Jakarta produces a total of 7,600 tons of waste per day, and as much as 61 percent of household waste. With the high rate of waste originating from households, SMEs create one of the innovations in overcoming household waste, called composter bin. Researcher choose her own company, PASMA, to be analyzed based on the problem. PASMA is a company that enters an environmentally friendly style that provides a composter bin and is equipped with technology that can transform organic waste, such as food waste, into something more valuable. However, the company faces several problems in forming SMEs, such as lack of funds, lack of background are related to the progress of science and technology, materials that keep changing and the consequence is that PASMA cannot sell products. Because of that, PASMA needs to have a business strategy, that is a movement and acts a company uses to attract customers, compete effectively, improve efficiency, and achieve organizational objectives. The purpose of this study is to improve business strategy in increasing product sales. This study use a qualitative method through interviews. Several external and internal factors in the conceptual framework will be used in designing interview questions. Based on the results of research in determining the selling price, market analysis is needed to get the desired target market and find out the market selling price from offline and online sources. Setting prices must consider what value of the product will be given to customers and start by calculating the production costs in advance. After the price is decided, cash flow projections will be made as to the main source for calculating capital budgeting. This study will be used to make cash flow projections for the next five years and generate NPV, IRR, and payback period in three planned scenarios. This research can still be developed as an improvisation of business strategies in increasing product sales in the next five years due to changing trends that affect changes in purchases in the future.